Letter to the editor: lansoprazole interferes with fungal respiration and acts synergistically with amphotericin B against multidrug-resistant Candida auris - Meng Zhu; Hongyang Wang; Yongsheng Zhang; Fuzhen Pan (Emerging Microbes and Infections)
The study investigates the potential of lansoprazole, a proton pump inhibitor, to interfere with fungal respiration and enhance the antifungal activity of amphotericin B against multidrug-resistant Candida auris. The authors administered lansoprazole at concentrations significantly higher than typical therapeutic doses, which demonstrated promising results but also raised concerns about potential toxicity. We suggest incorporating a control group, monitoring toxicity indicators, performing pathological examinations, and conducting cellular assays to improve the study's rigor and reliability. We also highlight the need for further research into the mechanisms of lansoprazole's antifungal activity, its long-term effects on amphotericin B resistance, and potential drug-drug interactions with amphotericin B. Addressing these concerns is crucial for the clinical translation of lansoprazole as an adjuvant to amphotericin B.